Optimization of torque in pole vaulting using genetic algorithm - Ohshima, S.; Ohtsuki, A. (The Engineering of sport 7, Volume 2, 2008)
Pole vaulting has progressed rapidly in terms of improved mechanical properties and better appearance by using poles made of flexible fiberglass material. Competitive pole vaulting requires specific characteristics that promote higher jumps. Analysis of the dynamics of pole vaulting basically requires a thorough consideration with the aim of having a high flexibility of the pole and all joint torque actions of the body. In this research, Simulation analysis to optimize the joint torque was done by using Genetic Algorithm. The System consists of a combination of a flexible pole and several links (vaulter). In the present genetic algorithm, the joint torque of the vaulter was expressed in terms of trigonometric functions. The expression for the torque was given by the amplitude, angular frequency and phase of the model equation. The overall evaluation function was the height and the control parameters were the joint torque, vaulter's speed, and pole stiffness. The result of the Optimum torque with respect to time readily obtained from our genetic algorithm show similar trend with published results obtained by inverse dynamic analysis.